Effects of Trained Peer vs. Teacher Feedback on EFL Students’ Writing Performance, Self-Efficacy, and Internalization of Motivation - Cui, Ying; Schunn, Christian D.; Gai, Xiaosong; Jiang, Ying; Wang, Zhe (Frontiers in Psychology, 2021)
Abstract This study investigated the longer-term impacts of trained peer feedback in comparison with teacher feedback on students’ writing development and writing motivation. Sections of an EFL writing course were randomly assigned to either teacher feedback or trained peer feedback conditions across two semesters. In the first semester, during their writing class, students either received training in how to implement peer feedback or simply studied models of writing (that were also used in the training work). In the second semester, students either received teacher or peer feedback across multiple assignments. Writing competence, writing self-efficacy, and writing self-regulated learning were assessed at the beginning and end of the second semester. Trained peer feedback and teacher feedback had similar positive effects on the improvement of writing competence and writing self-efficacy. However, trained peer feedback led to a significant enhancement of students' autonomous motivation relative to no such growth from teacher feedback.